2023
DOI: 10.1038/s41467-023-38467-9
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric consortium study demonstrates that dimethylarginine dimethylaminohydrolase 2 is not a dimethylarginine dimethylaminohydrolase

Vinitha N. Ragavan,
Pramod C. Nair,
Natalia Jarzebska
et al.

Abstract: Dimethylarginine dimethylaminohydrolase 1 (DDAH1) protects against cardiovascular disease by metabolising the risk factor asymmetric dimethylarginine (ADMA). However, the question whether the second DDAH isoform, DDAH2, directly metabolises ADMA has remained unanswered. Consequently, it is still unclear if DDAH2 may be a potential target for ADMA-lowering therapies or if drug development efforts should focus on DDAH2’s known physiological functions in mitochondrial fission, angiogenesis, vascular remodelling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…412W also reversed the loss of endothelium-dependent (NO) vasorelaxation in human saphenous artery. 17 , 30 Both effects demonstrate continual turnover of methylarginines, with DDAH1 ensuring the intracellular ADMA accumulation is not normally sufficient to block NO synthesis. We used the recently developed and selective DDAH1 inhibitor, L-257, which binds within the active site of the enzyme elevating ADMA sufficiently to inhibit NO signaling.…”
Section: Discussionmentioning
confidence: 99%
“…412W also reversed the loss of endothelium-dependent (NO) vasorelaxation in human saphenous artery. 17 , 30 Both effects demonstrate continual turnover of methylarginines, with DDAH1 ensuring the intracellular ADMA accumulation is not normally sufficient to block NO synthesis. We used the recently developed and selective DDAH1 inhibitor, L-257, which binds within the active site of the enzyme elevating ADMA sufficiently to inhibit NO signaling.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) [ 68 , 69 ]. After protein degradation, ADMA is either transformed to citrulline and dimethylamine by dimethylarginine dimethylaminohydrolase 1 (DDAH1) or transported into the extracellular compartment for remote DDAH1 metabolism or renal elimination [ 30 , [70] , [71] , [72] , [73] ]. Differently from ADMA, SDMA is not metabolised by DDAH1 and undergoes renal elimination [ 28 , 71 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that DDAH2 does not metabolize ADMA and may have an ADMA independent function. 15 Given previously known DDAH inhibitors were based on inhibiting ADMA conversion to citrulline, it is likely these compounds inhibit DDAH1 only.…”
Section: Introductionmentioning
confidence: 99%